ETHNOCENTRİSM AS A FACTOR AFFECTİNG VOLUNTARY TAX COMPLİANCE (Third Sector Social Economic Review, 2019)
In order to minimize the tax deficit, which is an important problem in terms of public finance, increasing tax compliance is at the beginning of the solution proposals. Increasing voluntary compliance in this context tax constitutes the agenda of all tax administrations. It is important to solve the tax deficit problem by reducing the tax compliance sensitivity to different variables. In reducing this sensitivity, determining the factors affecting tax compliance are among the requirements. In this study, voluntary compliance in consumption taxes, which has a relatively large share in the tax revenues of developing countries, were covered by ethnocentrism.
Keywords: Tax compliance; Voluntary tax compliance; Pariotism; Ethnocentrism.